Pemilihan Mitra Proyek PJU Tenaga Surya dengan Metode Analytical Hierarchy Process - Fauziah, Eva; Fasa, Nadia; Rahma, Rana Adila (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
In the current era of development, infrastructure is one of the main priorities of various countries, including Indonesia, in order to improve people's mobility. One of the initiatives. The Indonesian government is the Solar Street Lighting (PJU-TS) project, which is implemented by PT. Z as a provider. This study aims to determine the best partner for PT. Z in the Solar Street Lighting (PJU-TS) project in the North Sumatra region using the Analytical Hierarchy Process (AHP) method. PT. Z faces challenges in ensuring that the selected partner is able to meet important criteria such as price, financial capability, experience, and responsibility, considering that several previous partners failed to complete the project on target. Through the AHP method, this study analyzed three partners participating in the tender by conducting pairwise comparisons of each criterion. The results showed that responsibility was the main criterion in selecting a partner, followed by financial capability and experience. Based on the AHP calculation, PT. Organisasi Satu Solusi is a suitable partner to execute this project, as it excels in three main criteria: financial (0.219), experience (0.030), and responsibility (0.076).The AHP method has proven to be effective in facilitating a more structured and accurate decision-making process, providing PT. Z with a tool to select the right partner, thereby reducing the risk of delays and errors in the project. Keywords: Analytical Hierarchy Process, Partner Selection, PJU, Responsibility